Pollutant Burden in Autism Spectrum Disorder: Mechanistic Convergence, Genetic Susceptibility, and Clinical Translation - George Ayoub (Current Issues in Molecular Biology, 2026)
Autism spectrum disorder (ASD) risk reflects genetic susceptibility and modifiable environmental exposures acting during fetal and early postnatal critical periods. Building on our prior two-path model, in which folate receptor autoantibody-driven cerebral folate deficiency and oxidative stress/neuroinflammation converge on disrupted neurodevelopment, this review provides the first full mechanistic treatment of environmental pollutants within that framework. We synthesize evidence across seven exposure categories: micro/nanoplastics, plastic-associated endocrine-disrupting chemicals, ambient/indoor air pollution, tire wear particles and 6PPD-quinone, heavy metals and pesticides, industrial chemicals and persistent organic pollutants, and ultra-processed food intake as a parallel, non-pollutant contributor to the same inflammatory pathway. Human biomonitoring of micro/nanoplastics has progressed beyond detection in the placenta, brain and breast milk to direct evidence of placental genotoxicity and fetal endocrine disruption, complementing rodent data linking early-life exposure to impaired corticogenesis, disrupted microglial synaptic pruning, and ASD-relevant behavioral deficits. Across categories, oxidative stress, barrier disruption, neuroinflammation, endocrine disruption, and epigenetic modification recur as convergent mechanisms acting on trimester- and age-specific windows of vulnerability. Genetic variation in folate pathway and mitochondrial genes, as well as folate/vitamin B sufficiency, are proposed as candidate effect modifiers rather than established protective factors to modify susceptibility to this pollutant burden. Most evidence is associational or mechanistic rather than trial-based; we grade evidence strength and translate findings into biomarker-guided clinical and population-level policy guidance.